MENINGKATKAN PERKEMBANGAN MOTORIK ANAK USIA DINI MELALUI PARTISIPASI MULTIOLAHRAGA: PROGRAM PRASEKOLAH LONGITUDINAL USIA 4 HINGGA 6 TAHUN - Avrilliyah, Shofi Avrilliyah; Hariyanto, Agus Hariyanto; Siantoro, Gigih Siantoro; Pramono, Bayu Agung Pramono; Alkhadaf, Diego Muhamad Alkhadaf; Cahyaningrum, Viola Cahyaningrum (JURNAL ILMU KEOLAHRAGAAN, 2025)
This study aims to evaluate the effect of a multi-sport program on the motor development of early childhood (4-6 years old). The program consists of various physical activities such as throwing, catching, running, jumping, and balancing to improve basic motor skills. A total of 18 boys aged 4 to 6 years old participated in the study. The research design used was a One Group Pre-Post Design, with motor skills measured through pre-tests and post-tests. The data were analyzed using SPSS, with the Shapiro-Wilk normality test to ensure data distribution, as well as the Wilcoxon test and paired-sample t-test to test for significant differences between the pre-test and post-test. The results showed a significant improvement in the children's motor skills, with significant differences in all motor variables tested. These findings indicate that multi-sport programs can effectively improve the motor skills of young children, contributing to their physical and cognitive development.     Keyword: Motor Skills, Early Childhood; MOBAK-KG; Multisport Program